Aldo van Eyck’s Playgrounds: Aesthetics, Affordances, and Creativity - Withagen, Rob; Caljouw, Simone R. (Frontiers in Psychology, 2017)
After World War II, the Dutch architect Aldo van Eyck developed hundreds of playgrounds in the city of Amsterdam. These public playgrounds were located in parks, squares, and derelict sites, and consisted of minimalistic aesthetic play equipment that was supposed to stimulate the creativity of children. Over the last decades, these playgrounds have been studied by sociologists, theorists of art and architecture, and psychologists. Adopting an ecological approach to the human environment, it is argued that the abstract forms of van Eyck’s play sculptures indeed stimulate the creativity of the child. Whereas a slide or a swing almost dictates what a child is supposed to do, van Eyck’s play equipment invites the child to actively explore the numerous affordances (action possibilities) it provided. However, it is argued that the standardization (e.g. equal distances between blocks or bars) that tends to characterize van Eyck’ play equipment has negative effects on the playability. This standardization, which was arguably the result of the aesthetic motives of the designer, might be appealing to children when simply looking at the equipment, but it is not of overriding importance to them when playing in it. Indeed, a recent study indicates that the affordances provided by messy structures appear to have a greater appeal to playing children.